Experiencia en el diagnóstico y tratamiento del paciente con trauma maxilofacial por arma de fuego, en el servicio de cirugia maxilofacial del Hospital Universitario San Vicente de Paúl de Medellín entre 1998 y 2003 (2005)
ABSTRACT: The objective of this study is to present a descriptive and retrospective analysis of the behavior of trauma to the craniofacial complex produced by firearms in patients that consulted the Maxillofacial Surgery and Estomatologic Service of the San Vicente de Paul University Hospital (HUSVP) and the School of Dentistry of the University of Antioquia between the years1998 and 2003. The parameters considered were age, sex, type of firearm used, motive of aggression, and number of impacts received. If the patients were under the effects of alcohol or psychoactive drugs at the moment of injury were also evaluated. The type of injury caused to hard and soft tissues, type of treatment performed, complications and type of healing processes were studied as well. 137 patients examined with this type of traumatism presented the following findings: the most frequent age interval reported for this type of injury was between 21 and 30 years of age with 37% of the registered cases, 89% of the patients were males, 90% of the wounds were caused by pistols, assault was the motive in 58% of the aggressions, 89% of the patients never had antecedents of this type of traumatism, 50% of the patients presented a single bullet impact and 92 of the 137 patients had never consumed alcohol or drugs. The most common treatment was closing the injury, 39% of the cases and 28% of the patients received a combination of opening and closing, 88% of the patients didn’t present an infection during treatment and a correct healing process was observed in 72% of the patients. 60% of the patients required treatment for more than ten weeks before final discharge and 70% were see within the first five days at the Maxillofacial Surgery service after being injured. The most affected anatomical regions in the midface were the malar and dentoalveolar processes and the mandibular corpus and dentoalveolar process in the mandible.